2015
DOI: 10.3174/ajnr.a4547
|View full text |Cite
|
Sign up to set email alerts
|

GABA and Glutamate in Children with Primary Complex Motor Stereotypies: An1H-MRS Study at 7T

Abstract: Background and Purpose Complex motor stereotypies (CMS) are rhythmic, repetitive, fixed, purposeful but purposeless movements that stop with distraction. They can occur in otherwise normal healthy children (primary stereotypies), as well in those with autism spectrum disorders (secondary stereotypies). The underlying neurobiological basis for these movements is unknown, but thought to involve cortical-striatal-thalamo-cortical pathways. In order to further clarify potential neurochemical alterations, GABA, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
(44 reference statements)
0
35
0
3
Order By: Relevance
“…Prior studies in younger children with primary CMS 5 have shown a positive association between striatal GABA/Cr and SSS severity (but not ACC), perhaps suggesting the presence of a critical reduction in striatal projection neurons, beyond which there is no further impact on stereotypies. An additional potential explanation is that the expected correlation represents a developmental phenomenon, i.e., neurobiological changes associated with repetitive behavior may evolve over time.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Prior studies in younger children with primary CMS 5 have shown a positive association between striatal GABA/Cr and SSS severity (but not ACC), perhaps suggesting the presence of a critical reduction in striatal projection neurons, beyond which there is no further impact on stereotypies. An additional potential explanation is that the expected correlation represents a developmental phenomenon, i.e., neurobiological changes associated with repetitive behavior may evolve over time.…”
Section: Discussionmentioning
confidence: 91%
“…These findings are generally consistent with results identified in a younger cohort of children with primary CMS (ages 5–9 years) evaluated by single voxel MR spectroscopy. In the latter, affected children had a significant reduction of GABA, the inhibitory neurotransmitter of striatal projection neurons and striatal and cortical interneurons, within both the striatum and ACC, but not prefrontal or premotor cortex 5 . In contrast, our larger sample, including both boys and girls, differ from a smaller earlier study of solely boys with primary CMS 4 , which showed a reduction in caudate and frontal white matter volumes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Few studies, however, have employed ultra-high imaging in pediatric populations, and (to our knowledge) only one study has used MRS at 7 T in children under age 10 years (Harris et al, 2016). Among published studies, there is variability in reported findings within 3 T protocols and differences between 3 T and 7 T MRS investigations of TS (see Table 1).…”
Section: Introductionmentioning
confidence: 99%